Penegakan Hukum Terhadap Tindak Pidana Juru Parkir Liar Di Kota Palembang - Akrim Mualif Alfatiri; Wawan Indrawan; Joni; Firmansyah (Lex Stricta : Jurnal Ilmu Hukum, 2024)
Parking is an important part of the transportation system, as every private vehicle journey typically begins and ends at a parking lot. The government regulates various forms of parking permits, such as public parking, incidental parking, special parking, parking lots, parking buildings, and parking pools. However, the practice of illegal parking fees still frequently occurs and is categorized as illegal extortion (pungli). Under the Criminal Code (KUHP), such extortion can be prosecuted under Article 368 on extortion, which imposes a prison sentence of up to nine months on offenders who force someone to hand over property or money unlawfully through violence or threats.